Managing in organisations : a practical guide - Elsworth, Tom (Routledge, 2025)
"Managing in Organisations is a concise, accessible and practical approach to the difficult job of line management. It offers a kit of management tools and a range of worked examples that can be used to address the key tasks that managers face in the workplace. The book provides clear insights into how people behave everyday in real organisations. The fundamentals of key theories and sources is covered throughout for those coming to the subject for the first time. Topics covered include: Individual, group and team organisational behaviour, organisational culture and diversity, supervision and leadership, organisational design, management and change, and governance. The book considers small and larger enterprises as well as public, private and third sectors. Short cases link the issues in the chapter and provide opportunities for developing skills and discussion. This book provides an introduction to the world of managing in organisations and is suitable for those study organisational behaviour, organisational studies, management and human resource management. It will also be very useful to the entrepreneur planning a small start-up and to the busy manager of a small or medium sized enterprise seeking to understand how best to manage the organisation for performance"-- Provided by publisher.
Keywords: Management.; Executive ability.; Organizational behavior.; Organizational effectiveness.; elektronické knihy; electronic books